Towards a Catholic North America? Projections of religion in Canada and the US beyond the mid-21st century - Anne Goujon; Eric Caron Malenfant; Vegard Skirbekk (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2012)
Religion and religiosity are important identity markers, and changes in a country's religious composition may affect its culture, value orientations and policies. In recent decades the Protestants in both the US and Canada have lost their absolute population majority. In the present study we investigate the future of the religious composition in both the US and Canada jointly until the 2060s taking into consideration changes due to demographic forces, the level and composition of migration, fertility differentials and intergenerational religious transmissions. The joint focus on both the US and Canada allows one to better understand the commonalities and differences between these two nations which are tightly knit in terms of geography, politics, economics and culture. The projections reveal that North America should not become Catholic by mid-century but close to, with an increasing importance of minorities in the religious landscape.
Keywords: 300; Religion; religious composition; transmission of religion; secularization; multistate projections; Katholizismus; Sozialer Wandel; Prognose; Bevölkerungsentwicklung; USA; Kanada